Emily Jackson - Jackson, Emily (Atuanui Press, 2016)
A memoir told in the painter's own words selected from her private journals and letters, Emily Jackson: A Painter's Landscape reveals the inner life of a passionate and driven artist as well as giving an insightful glimpse into the Auckland arts scene of the 1970s, '80s and '90s.